Investigation of Cascading Adsorption Refrigeration System with Integrated Evaporator-Condenser Heat Exchanger Using Different Working Pairs. (August 2015) - Dakkama, H.J.; Elsayed, A.; Al-Dadah, R.K.; Mahmoud, S.M.; Youssef, P.
Abstract: This paper investigates the performance of various adsorbent/refrigerant working pairs in a cascaded adsorption system using Simulink/Matlab software. The cascaded system consists of two pairs of adsorber beds, condenser, evaporator and an integrated condenser/evaporator heat exchanger, forming upper and bottoming cycles. Four combinations of working pairs were investigated: ATO-Ethanol + Maxsorb/R507A, Maxorb/R134a + Maxorb/Propane and ATO/Ethanol + Maxorb/Propane and Maxorb/R134a + Maxsorb/R507A. The latter case was used for validation and as a reference point for assessing the performance of the investigated working pairs in term of COP and cooling capacity. Results showed that the Maxorb/R134a + Maxorb/Propane combination gives a higher enhancement compared to reference one with up to 30.0% and 30.1% for the COP and cooling capacity, respectively. ATO/Ethanol + Maxorb/Propane combination is the cheapest but with lower performance.